A DAMAGE ANALYSIS OF FRONT FINAL DRIVE PLANETARY GEAR BACKHOE LOADER CASE 580 SN - Hairian Rahmadi; SUDIRMAN (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Today's technology continues to develop and these developments are applied to the field of heavy equipment, therefore it is necessary to analyze one of the components of the Backhoe Loader Case 580SN heavy equipment unit, namely the Front Final Drive Planetary Gear. The Backhoe Loader is one of the heavy equipment units designed to be able to carry out one of the functions and activities of the construction process which is heavy when carried out by human labor, such as: transporting, lifting, loading, moving, digging, mixing, and so on in an easy, fast, efficient and safe way. This research method analyzes and directs spaciousness, this is because this company has a lot of heavy equipment, one of which is the Backhoe Loader which is the object of research. The results of field analysis Damage to the Front Final Drive Planetary Gear Backhoe Loader Case 580 SN is caused by a lack of Final Drive lubricant when the unit is running, this is because the O-Ring Final Drive is wearing out so that the lubricant seeps out.